Preparation and characterisation of Pt-containing polyelectrolyte membranes for catalytic and separation processes - Michaels, Wynoma Chantal (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc.) -- University of Stellenbosch, 1998.